2021
DOI: 10.1080/13102818.2021.1892526
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomics profiling and antimicrobial activity of fermented date fruit (Khastawi) used as functional ingredients for making Asian confectionary (Dodol)

Abstract: Date fruit (Phoenix dactylifera) have long history in food application due to the nutritional value, pleasant flavour and biological activity. This study aimed at investigating the antimicrobial activity of date fruits fermented with Lactobacillus plantarum ATCC8014. The fermented date fruit was added as ingredient for confectionary making and evaluated for it is effects on the physiochemical properties and shelf life of toffee-like South Asian product (Dodol). The results showed broad range antifungal activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Other studies have reported an increase in the concentration of polar amino acids, including glutamic acid, aspartic acid, serine, histidine, and cysteine, following protein fraction hydrolysis by LAB, which may contribute to enhanced HO• activity [ 75 ]. In a previous study, several bioactive metabolites, namely propylene glycol, lactic acid, acetic acid, acetoin, and GABA, were identified as having potential antibacterial effects against various pathogens [ 76 , 77 ].…”
Section: Resultsmentioning
confidence: 99%
“…Other studies have reported an increase in the concentration of polar amino acids, including glutamic acid, aspartic acid, serine, histidine, and cysteine, following protein fraction hydrolysis by LAB, which may contribute to enhanced HO• activity [ 75 ]. In a previous study, several bioactive metabolites, namely propylene glycol, lactic acid, acetic acid, acetoin, and GABA, were identified as having potential antibacterial effects against various pathogens [ 76 , 77 ].…”
Section: Resultsmentioning
confidence: 99%
“…Interesting work has been done on the usage of fermented date fruits for the production of Dodol, an Asian confectionary. This work shows how fermented dates fruits (Khastawi) can be used for the production of bakery products and confectionaries (Muhialdin et al, 2021). In the case of Dodol, the addition of fermented date not only extends the shelf life of products but also increases nutritional qualities and bioactive compounds.…”
Section: Role Of Metabolomics In the Enhancement Of Flavor Compoundsmentioning
confidence: 97%
“…1 H NMR metabolomics study helps to identify bioactive metabolites in fermented date fruits. Propylene glycol, lactic acid, acetic acid, acetoin, and γ-Aminobutyric acid are some of the bioactive compounds identified in fermented dates (Muhialdin et al, 2021). Homovanillin, 6, 7-Benzocoumarin, Gentisyl alcohol, and 2, 5-Dihydroxyanisol were higher in unhopped beer when fermented with probiotic strains L. paracasei Lpc-37 and S. cerevisiae CNCM I-3856 (Loh et al, 2021).…”
Section: Identification Of Bioactive Metabolitesmentioning
confidence: 99%
“…A gooey, luscious, and firm texture is preferable for consumer acceptance [ 40 ]. Numerous factors influencing the quality and shelf-life of coconut milk candy, including the cooking temperature, heating time, humectants, sugar quantity, and types of sugar, have been investigated to improve the texture of the developed coconut caramel candy [ 37 , 39 , 40 , 41 , 42 , 43 ] to be soft and chewy but have low stickiness. Nevertheless, despite the processing conditions, a deterioration in quality, particularly texture hardening, was still evident during storage, resulting in coconut milk candy having a short shelf life of 7 to 14 days [ 39 , 40 ].…”
Section: Introductionmentioning
confidence: 99%